Metode Pengasuh dalam Pembentukan Karakter Religius Anak Panti Asuhan Aisyiyah Putra - Yulistia, Duwik; Elviana, Elviana; Ardizon, Cilung (Darul Yasin Al Sys, 2024)
Character Education aim to shape and build thought patterns. Attidute and behavioral of foster children to become positrif individual, good Morals, honest and responsible. Religius character is needed and needed so that foster children have a religius spirit. Religius character needs be formed by getting used religius activities in orphanages. The child's character is closely related to the upbringing received from his caregiver, in other words, good parenting will also have a positive impact on the child and the character of a child is a reflection of the parenting style provide by the caregiver. In order to prevent character deviantion from occurring in children, good caregiver need several methods in farming religius charater children. This reseach aims to analyze the parenting stlye applice by the Aisyiyah Putra Bukittinggi Orphanage in children. This reseach uses qualitative descriptive research which draws from observasi and interviews at the Putra Muhammdiyah Orphane in Bukittinggi. The results of this research show that the Muhammadiyah Putra Bukittinggi. Orpahanage uses the exemplary method, and other methods in inviting people to form worship, education (indriting congration prayers , Providing schedules for congregation prayers and taking tursn in adhan) , Sosial interaction . This method adheres to principles of the Asyiyah Putra Orphanege’s caregiving patters which is based on the Qur’an.